Research trends on Maqasid Shariah and Islamic rural banks: a bibliometric investigation - Syarifah, Lailatis; Rosman, Romzie; Nasution, Atiqi Chollisni; Mohd Yusoff, Syarah Syahira (UIS, 2025)
This study explores the integration of Maqasid Shariah principles into the performance of Islamic Rural Banks (IRBs) and Islamic Microfinance (IsMF) through bibliometric analysis and systematic literature review. A total of 35 relevant journal articles published between 2006 and 2025 were analyzed using tools such as Publish or Perish (PoP), VOSviewer, and Mendeley. The findings reveal a growing interest in using Maqasid Shariah not only as a performance measurement tool but also as a guiding philosophy in social impact, governance, financial inclusion, and integration with Sustainable Development Goals (SDGs). The research trend highlights a shift from conceptual discussions to strategic and operational applications. However, the implementation remains fragmented and underdeveloped. This paper contributes by identifying dominant themes, research gaps, and future research directions to enhance the role of IRBs and IsMFs in achieving ethical, inclusive, and sustainable Islamic finance.